2020
DOI: 10.1155/2020/5852760
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Variability in the Hydrometeorological Time-Series over Upper Indus River Basin of Pakistan

Abstract: This paper investigates the spatiotemporal variability in hydrometeorological time-series to evaluate the current and future scenarios of water resources availability from upper Indus basin (UIB). Mann–Kendall and Sen’s slope estimator tests were used to analyze the variability in the temperature, precipitation, and streamflow time-series data at 27 meteorological stations and 34 hydrological stations for the period of 1963 to 2014. The time-series data of entire study period were divided into two equal subser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
21
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 46 publications
9
21
0
Order By: Relevance
“…The change point analysis marked significant variation in streamflow for Bunji and Astore river. The finding of this study is also consistent with a recent study (Yaseen et al 2020).…”
Section: Variability and Trends Of The Discharge In Upper Indus Basinsupporting
confidence: 94%
“…The change point analysis marked significant variation in streamflow for Bunji and Astore river. The finding of this study is also consistent with a recent study (Yaseen et al 2020).…”
Section: Variability and Trends Of The Discharge In Upper Indus Basinsupporting
confidence: 94%
“…Therefore, a low-warming MS in the UIB at the end of the 21st century is possible and may further extend into the high-altitude regions under the same MS forcing. Many earlier studies, e.g., [32,33,35,37] have shown MS cooling tendencies. Although our model-ensemble did not show MS cooling except over one region, some of the individual models projected some cooling.…”
Section: Ms Projectionsmentioning
confidence: 88%
“…Note that the humidity predictors dominate the PMS regression models (Table 4), and, therefore, future changes in atmospheric humidity will strongly influence the regional temperatures. Previous studies, e.g., [33,36,39], also projected PMS warming over the UIB through T max changes.…”
Section: Pms Projectionsmentioning
confidence: 92%
See 1 more Smart Citation
“…11). The studies of Yaseen et al (2020) reported a spatiotemporal variation in temperature trends over the UIB. As UIB consists of Shyok and Shigar, Astore and Haunza, Gilgit, Jehlum, and Kabul sub-basin as part of UIB, which have different elevations, regions with low altitude face the warming trend, and the areas with high altitude show the cooling trends.…”
Section: Data and Analysismentioning
confidence: 99%